Persistent Müllerian duct syndrome diagnosed incidentally: a case report - Fatima, Nazish; Kiran, Zareen; Shabbir, Khalil Ullah; Baloch, Akhtar Ali (Journal of the Pakistan Medical Association, 2023)
Persistent Müllerian Duct syndrome is a rare male disorder of sexual development. The phenotypically and genotypically male patient presents with female internal organs (i.e., uterus, cervix, fallopian tubes and upper part of vagina) due to deficiency of anti-mullerian hormone or insensitivity of tissues to Anti Mullerian Hormone. We present a 19 year old male who came with complaint of right iliac fossa pain. He was investigated for acute appendicitis and on imaging, he was diagnosed to have bilateral cryptorchidism with rudimentary uterus. Computed tomography followed by pelvic ultrasonography was done which indicated two testes in abdomen and a soft tissue density structure, identified as a rudimentary uterus located posterior to the urinary bladder. CT scan findings were further confirmed by magnetic resonance imaging pelvis. A trial of stepwise orchidopexy followed by orchidectomy with removal of rudimentary uterus was performed laparoscopically. —Continue